2021
DOI: 10.1088/1757-899x/1047/1/012082
|View full text |Cite
|
Sign up to set email alerts
|

Tree retraining in the decision tree learning algorithm

Abstract: Decision trees belong to the most effective classification methods. The main advantage of decision trees is a simple and user-friendly interpretation of the results obtained. But despite its well-known advantages the method has some disadvantages as well. One of them is that decision tree learning algorithm build an “almost optimal” tree. The paper considers the way to improve the efficiency of decision trees. The paper proposes a modification of decision tree learning algorithms by retraining the part of tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Recognition of the urban landscape. The paper compares the best results of the standard compositions considered in (Mitrofanov & Semenkin, 2021) with the proposed approach (EGP).…”
Section: Resultsmentioning
confidence: 99%
“…Recognition of the urban landscape. The paper compares the best results of the standard compositions considered in (Mitrofanov & Semenkin, 2021) with the proposed approach (EGP).…”
Section: Resultsmentioning
confidence: 99%
“…Various filtering methods have been previously studied and tested to select a separation feature [8]. The results of practical tests showed that the most suitable methods may differ depending on the specific application.…”
Section: Two-level Optimization Approachmentioning
confidence: 99%
“…During the process of creating a decision tree, various problems arise, each of which must be solved. One of the main problems is the choice of an attribute [7] by which division will be made at a given node (partition attribute).…”
Section: Introductionmentioning
confidence: 99%
“…Further, consider the efficiency of differential evolution application in solving various problems of classification by decision trees. Two of the most popular decision tree training methods were chosen for the study, i.e., ID3 and CART (Mitrofanov & Semenkin, 2021). The author calls an algorithm where the selection of the threshold value is carried out by enumeration as a basic algorithm.…”
Section: Efficiency Of Differential Evolution Application In Solving ...mentioning
confidence: 99%